2019
DOI: 10.6065/apem.2019.24.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Morning basal luteinizing hormone, a good screening tool for diagnosing central precocious puberty

Abstract: Purpose The standard method used to diagnose central precocious puberty (CPP) is the gonadotropin releasing hormone stimulation test (GnRHST). However, this test is inconvenient for children because it is time-consuming and requires multiple samples. This study aimed to determine the reliability of morning unstimulated luteinizing hormone (mLH) level when screening for CPP, with an emphasis on the influence of diurnal variation. Methods This study included 160 girls wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Pubertal development and body growth should be examined every 3 to 6 months, and repeated blood tests are not necessary if the uLH or uLH-to-uFSH ratio is not elevated ( 27 ). By no means should clinical manifestations of pubertal regression or arrest be given priority over hormonal tests because the probability of a positive GnRHST response after GnRHST increases with the increasing difference between bone age and chronological age ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pubertal development and body growth should be examined every 3 to 6 months, and repeated blood tests are not necessary if the uLH or uLH-to-uFSH ratio is not elevated ( 27 ). By no means should clinical manifestations of pubertal regression or arrest be given priority over hormonal tests because the probability of a positive GnRHST response after GnRHST increases with the increasing difference between bone age and chronological age ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to find a more acceptable and widely available alternative to the GnRH-stimulation test. Some researchers have proposed LH > 0.2–0.3 mIU/L from a random blood sample as a reliable screening cut-off for CPP ( 6 , 23 , 24 ). The present study also assessed the diagnostic utility of basal LH levels and found that the cut-off point was 0.255 mIU/L (sensitivity 68.9%, specificity 86.0%), which is similar to the cut-off points found in previous reports ( 1 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there were no significant differences in weight, height, BMI, and growth velocity between both groups; only advanced bone age emerged as a significant predictor of CPP in this age group, although with limited discriminatory capacity (positive predictive value: 69.5%). Therefore, an exclusive measurement of the auxological characteristics would not be sufficient to diagnose or exclude CPP in girls with breast budding in this age range ( 18 ). In addition, it should be noted that the prognosis of adult height of the CPP girls, which at the time of diagnosis is usually overvalued by clinical and auxological conditions ( 19 ), did not differ from that calculated for the PT girls.…”
Section: Discussionmentioning
confidence: 99%